2016
DOI: 10.1016/j.micres.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacteria—Insight into clinical outcomes and mechanisms of its probiotic action

Abstract: The invasion of pathogens causes a disruption of the gut homeostasis. Innate immune responses and those triggered by endogenous microbiota form the first line of defence in our body. Pathogens often successfully overcome the resistances offered, calling for therapeutic intervention. Conventional strategy involving antibiotics might eradicate pathogens, but often leave the gut uncolonised and susceptible to recurrences. Probiotic supplements are useful alternatives. Bifidobacterium is one of widely studied prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
110
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 146 publications
1
110
0
1
Order By: Relevance
“…Indeed, the beneficial effects of a single probiotic strain (Lb102 or Bfl41) on intestinal health may also be related to direct modulation of epithelial cell function, as suggested by our findings of increased expression of key colonic markers involved in the gut‐permeability and mucus‐layer integrity. Indeed, previous experiments demonstrated that both B. animalis and L. rhamnosus species are able to produce metabolites that exhibit cytoprotective roles in intestinal epithelial cells (57, 58). More profound changes in the gut microbiota composition may occur after administration of multiple probiotic strains, combined or not with prebi‐otics, as previously shown for the VSL#3 cocktail that contains 8 different strains (15).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the beneficial effects of a single probiotic strain (Lb102 or Bfl41) on intestinal health may also be related to direct modulation of epithelial cell function, as suggested by our findings of increased expression of key colonic markers involved in the gut‐permeability and mucus‐layer integrity. Indeed, previous experiments demonstrated that both B. animalis and L. rhamnosus species are able to produce metabolites that exhibit cytoprotective roles in intestinal epithelial cells (57, 58). More profound changes in the gut microbiota composition may occur after administration of multiple probiotic strains, combined or not with prebi‐otics, as previously shown for the VSL#3 cocktail that contains 8 different strains (15).…”
Section: Resultsmentioning
confidence: 99%
“…This study for the first time, the bifidobacteria were encapsulated and added as a functional starter culture in the meat products, and the results confirmed that a certain number (approximately 50%) of encapsulated probiotic B. longum could survive in the final products. The intake of probiotic bifidobacteria or foods containing these probiotic bacteria has been associated with a variety of health-promoting benefits (Sarkar and Mandal, 2016). Moreover, fermented sausage is the most popular and widely consumed meat product in many countries (Oliveira et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…(2) Some strains may reduce antibiotic-associated side effects and improve compliance to therapy. Moreover, pre- and probiotic supplementation may have immunomodulatory effects on the hosts as experimental studies demonstrated their anti-inflammatory effects in chronic inflammatory diseases like asthma, topical allergies, and inflammatory bowel disease [33, 34]. …”
Section: Discussionmentioning
confidence: 99%